ANALISIS SIFAT MEKANIK DAN STRUKTUR MIKRO HASIL PROSES HYDROFORMING PADA MATERIAL TEMBAGA (Cu) C84800 DAN ALUMINIUM Al 6063 - Majanasastra, R. Bagus Suryasa (Jurnal Ilmiah Teknik Mesin, 2016)
Hydroforming is one of many types of the formation process that uses molds with variable high-pressure compacting (hydraulic fluid) to provide pressure and filling the space fit the mold. In this study hydroforming process is done on a pipe made from copper and aluminum alloys C84800 6063 in order to generate changes inmost pipe diameter according to cetakannya.Goal of this study was to determine the mechanical strength of the ridge on the hydroforming process products with materials of copper and aluminum, for determine the microstructure in the bulge pipe produced using metallographic test and to determine whether there is a crack on the bulge and surrounding area. The imposition of this research is done with a variable maximum pressure of 10 tons. Material of sample consisted of three samples of each type of material, divided into several parts, the left, middle and right side. Analysis of this study showed that the mechanical strength on Cu C84800 copper pipe and Aluminium 6063 has good ductility, seen from the microstructure results hydroforming process proeutektik Î± (Cu-Zn) and copper phase and phase Î² on Al-Î± on aluminum. Microstructure of Copper C84800 is proetektik form Î±-phase (Cu-Zn) and Î² phase (brass), no visible cracks or defects. Micro structure of Aluminium 6063 form the main phase of Al-Î± globular shaped particles surrounded Mg2Si, no visible cracks or defects. From the results of hardness test using Vickers Hardness, Copper Cu C84800 Sample B samples have higher hardness values compared to other samples. From the results of hardness test using Vickers Hardness, At Aluminium 6063 sample, the ample A has a higher hardness values compared to other samples.